ANALISIS PERAN FUNCTIONAL BENEFITS, SYMBOLIC BENEFITS, EXPERIENTIAL BENEFITS DAN CUSTOMER SATISFACTION SEBAGAI PEMBENTUK LOYALTY INTENTION PADA CUSTOMER THE BODY SHOP (TELAAH PADA: THE BODY SHOP DI WILAYAH JAKARTA) - Santi Rimadias; Farah Safira Rachmayanti (Jurnal Ilmu Manajemen & Ekonomika, 2015)
The purpose of this research was conducted to identify the effect of functional benefits, symbolic benefits, experiential benefits and customer satisfaction towards loyalty intention from the customer who use The Body Shop.With a high market demand on cosmetics nowadays, producers are required to compete to meet costumer's expectations. This research was a quantitative descriptive research. There were 153 respondents which were gathered by convenience sampling.The results showed that functional benefits, symbolic benefits and experiential benefits had a positive and significant affect toward customer satisfaction. Furthermore, this research also showed that customer satisfaction had a positive and significant effect on loyalty intention.Keywords: loyalty intention, customer satisfaction, symbolic benefits, functional benefits, experiential benefits.